Incidence and risk factors of hepatocellular carcinoma in patients with hepatic venous outflow tract obstruction - Shashi Bala Paul; S. Shalimar; Vishnubhatla Sreenivas; Shivanand Gamanagatti; Hanuman Prasad Sharma; Ekta Dhamija; Subrat Kumar Acharya (2015)
Frequency of hepatocellular carcinoma (HCC) in hepatic venous outflow tract obstruction (HVOTO) is unclear and risk factors in HVOTO associated with HCC are unknown.To assess the incidence of HCC and to identify risk factors for HCC in primary HVOTO.In the consecutive primary HVOTO patients evaluated between 1989 to 2013, the incidence of HCC among HVOTO was assessed in a retrospective cohort study and identification of the risk factors for HCC in HVOTO patients done by a case-control study.Of the 421 HVOTO patients, 8 had HCC at presentation (prevalence 1.9%). Another 8 of the remaining 413 developed HCC during 2076.2 person-years follow-up (mean 5.03 + 4.65 years, range 0.08-20 years). The cumulative incidence of HCC was 3.5% (95% CI 1.28-9.2%) at 10 years. The case-control study included 16 HCC as cases and remaining 405 as controls. Controls were predominantly males (M:F - 230:175), mean age 29 ± 10.3 years. Cases were predominantly females with an older age of 36.2 ± 11.4 years (P < 0.01, OR = 1.06, CI 1.0-1.10%). Presence of cirrhosis (P < 0.001), combined inferior vena cava (IVC) and hepatic vein (HV) block (P < 0.03, OR = 5.58, CI 1.43-25.30%) and long-segment IVC block (P < 0.02, OR = 6.50, CI 1.32-32.0%) were significantly higher among cases than controls.Hepatic venous outflow tract obstruction is a risk factor for HCC. The cumulative incidence of HCC in HVOTO is low and progressively increases over time. Those with liver cirrhosis, combined IVC and HV block and long-segment IVC block are at risk to develop HCC and need active surveillance.